Blood in the water: The value of antitakeover provisions during market shocks - Guernsey, Scott; Sepe, Simone M.; Serfling, Matthew (Journal of Financial Economics, 2022)
During market-wide shocks that cause large drops in stock prices, firms with more state-endorsed antitakeover provisions (ATPs) experience smaller declines in value. Two channels appear to drive this finding. First, by giving boards more bargaining power to fight opportunistic bids, firms with more ATPs extract higher takeover premiums during market shocks. Second, having more ATPs attenuates the effect of market shocks on firm value by protecting relationship-specific investments with stakeholders from disruptive takeovers. Our results suggest that ATPs benefit shareholders during market shocks when firm values are abnormally low and represent one advantage of incorporating in states with more ATPs.